Serological diagnosis of cystic echinococcosis in cattle - Bulashev, Aitbay K; Suranshiev, Zhanbolat A; Akibekov, Orken S; Akanova, Zhanara Zh; Abulgazimova, Gulmira A (Folia parasitologica, 2017)
An IgM murine monoclonal antibody (MAb) was obtained against the excretory-secretory antigen (ES-Ag) of in vitro reared protoscoleces of Echinococcus granulosus (Batsch, 1786). Western blotting revealed that the MAb recognised a 20.6 kDa protein of this ES-Ag. The MAb was used in sandwich enzyme-linked immunosorbent assay (s-ELISA) for selective sensitisation of the solid phase with the protoscolex-specific protein from its ES-Ag and somatic antigen (S-Ag) to examine serum samples of 108 cows from a cystic echinococcosis (CE) endemic area for specific antibodies and to compare the results with those from necropsies and an indirect ELISA (i-ELISA). The sensitivity of s-ELISA/ES-Ag, s-ELISA/S-Ag and i-ELISA/S-Ag was 48%, 52% and 62%, respectively. The low sensitivity of the ELISA was probably caused by the fact that 13 cows (62%) were infected with sterile cysts (acephalocysts and/or calcified foci) only. A relatively high specificity (80%) of s-ELISA/ES-Ag was observed in cows with fertile cysts. It also detected antibodies in the serum of two cows that had recovered from the disease according to the necropsy. The i-ELISA/S-Ag gave false results in testing sera from a healthy animal and from a cow with tubercular foci. Further analysis will be necessary to define more precisely the value of this study, because the duration of antibody elimination from the bloodstream of recovered cattle remains unknown. The solution of this problem will increase the specificity of the proposed test in monitoring herbivorous animals for CE.
Keywords: Cattle; nemoci skotu; monoklonální protilátky; Cattle Diseases; Immunoglobulin M; imunoglobulin M; skot; echinokokóza; antigeny helmintové; ELISA; Echinococcosis; Enzyme-Linked Immunosorbent Assay; Animals; ženské pohlaví; zvířata; Sensitivity and Specificity; senzitivita a specificita; Antigens, Helminth; Antibodies, Monoclonal; Female; Echinococcus granulosus